2017
DOI: 10.22499/3.6604.002
|View full text |Cite
|
Sign up to set email alerts
|

A vertical wind structure that leads to extreme rainfall and major flooding in southeast Australia

Abstract: Here we examine winds associated with extreme rainfall and major flooding in coastal catchments and more broadly over southeastern Australia. Both radiosonde and re-analysis data are examined. In every case (i) atmospheric moisture content is high and (ii) the low-level winds are onshore, and in almost every case (iii) the wind-direction turns anti-cyclonically with increasing height up to 500 hPa. Data from Brisbane extending back more than 50 years is consistent with this behavior: winds turn anti-cyclonical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…At the latter two stations, upper-only cyclone collectively explain approximately 30% of 99th percentile days. This likely reflects the important role of 500 hPa geostrophic winds in the generation of heavy rainfall on days with prevailing onshore flow in these regions (Callaghan and Power 2017).…”
Section: Association Of Cyclones With East Coast Heavy Rainmentioning
confidence: 96%
“…At the latter two stations, upper-only cyclone collectively explain approximately 30% of 99th percentile days. This likely reflects the important role of 500 hPa geostrophic winds in the generation of heavy rainfall on days with prevailing onshore flow in these regions (Callaghan and Power 2017).…”
Section: Association Of Cyclones With East Coast Heavy Rainmentioning
confidence: 96%
“…For the TC Dora (2007) case, Leroux et al (2013) showed that PV injection at mid-levels from a mid-latitude cut-off low or PV coherent structure could help rapid intensification by increasing convection on the downshear side and sustaining the formation of an eyewall replacement cycle (PV budget analysis). They also noticed that the general 850-200 hPa shear was not indicative of rapid intensification and that it would be more appropriate to use the 850-500 hPa shear in some cases, which was confirmed in the recent study of Colomb et al (2019).…”
Section: Introductionmentioning
confidence: 72%
“…The centre of ex-TC Oswald was located just to the north-west of Townsville with radar indicating moderate patchy rain along the coast to the south, where the 700-hPa flow was directed from the warm side of the 850-500-hPa vertical wind shear to the cold side of it (Fig. 7b), implying WAA or moist isentropic ascent and heavy rainfall (Callaghan 2017a(Callaghan , 2017bCallaghan and Power 2016;Callaghan and Tory 2014;Tory 2014). A nice illustration is to look at Brisbane airport at 2300 UTC 26 January when storm force winds are turning anticyclonically with height from 850 to 500 hPa (Fig.…”
Section: Thermodynamic and Kinematic Structures Of Ex-tropical Cyclonmentioning
confidence: 99%
“…Goff and Hanson (2012) found this to be the case in the middle latitudes of the US. Previous studies (Bonell et al 2005;Bonell and Callaghan 2008;Callaghan and Tory 2014;Tory 2014;Callaghan and Power 2016) examined winds associated with extreme rainfall in both the tropics and the mid-latitudes of Australia. Further studies (Callaghan 2017a(Callaghan , 2019 found this to apply in many cases around the globe.…”
Section: Mechanisms Which Produce Extreme Rainfallmentioning
confidence: 99%
“…In every case (i) atmospheric moisture content was high and (ii) the low-level winds were onshore, and in almost every case (iii) the wind-direction turned anticyclonically with increasing height up to 500 hPa. Further details of this wind structure can be found in Callaghan and Power (2016).…”
Section: Mechanisms Which Produce Extreme Rainfallmentioning
confidence: 99%